The effect of the W-shape stirrups shear reinforcement on the dynamic behavior of RC flat solid slab subjected to the low-velocity impact loading - Al-Dala'ien R.N.; Syamsir A.; Usman F.; Abdullah M.J. (Elsevier B.V., 2024)
Reinforced concrete flat solid slabs may experience explosive and impact loads. Reinforced concrete flat solid slabs have been studied under static and dynamic loads. Researchers have widely explored numerous reinforcing strategies to strengthen RC slabs exposed to impact loads, yet gaps remain. Internal anchorage stirrups (W-stirrups shear reinforcement) is still rarely used to strengthen slabs against impact loading. Consequently, this study emphasized the influence of W-stirrups shear reinforcement on the dynamic response and failure modes of RC slabs subjected to impact loads. The first part examined the impact behavior of fully fixed RC flat solid slabs reinforced with W-stirrups shear reinforcement experimentally. Slabs were impacted using portable drop-weight testing equipment. Six 800-x-800-x-90-mm RC slabs were made. Three samples were reinforced with a W-stirrups orthogonally oriented in two directions, whereas three controls were without any type of strengthening. The eccentric vertical displacement of slabs, strain at four points on the W-stirrups, two on main steel, and two on concrete, and acceleration at one point over a slab were measured